Propuesta de pausas activas en una IPS de Bogotá (2021)
The aim of this document is to analyze the main factors by which the employees and/or collaborators do not take active breaks or do them in an inappropriate way at the CUIDARTE TU SALUD S.A.S. Institution. The research project was established by the researchers after observing that there is no evidence of any strategy or program defined or applied in order to encourage the workers of this IPS to autonomously carry out active breaks. Furthermore, the lack of knowledge of the risks and consequences after the development of their activity (drivers, health care personnel and administrative personnel) was also reflected.